Maintenance of cutaneomuscular neuronal excitability after leg-cycling predicts lower limb muscle strength after incomplete spinal cord injury. Issue 6 (June 2016) - Piazza, Stefano; Gómez-Soriano, Julio; Bravo-Esteban, Elisabeth; Torricelli, Diego; Avila-Martin, Gerardo; Galan-Arriero, Iriana; Pons, José Luis; Taylor, Julian
Highlights: Rhythmic leg exercise changes spinal neuronal activity after spinal cord injury (SCI). Leg-cycling may improve cutaneous sensorimotor function after incomplete SCI. Cutaneous sensorimotor function after leg-cycling predicts leg strength after iSCI. Abstract: Objective: Controlled leg-cycling modulates H-reflex activity after spinal cord injury (SCI). Preserved cutaneomuscular reflex activity is also essential for recovery of residual motor function after SCI. Here the effect of a single leg-cycling session was assessed on cutaneomuscular-conditioned H-reflex excitability in relation to residual lower limb muscle function after incomplete SCI (iSCI). Methods: Modulation of Soleus H-reflex activity was evaluated following ipsilateral plantar electrical stimulation applied at 25–100 ms inter-stimulus intervals (ISI's), before and after leg-cycling in ten healthy individuals and nine subjects with iSCI. Results: Leg-cycling in healthy subjects increased cutaneomuscular-conditioned H-reflex excitability between 25 and 75 ms ISI ( p  < 0.001), compared to a small loss of excitability at 75 ms ISI after iSCI ( p  < 0.05). In addition, change in cutaneomuscular-conditioned H-reflex excitability at 50 ms and 75 ms ISI in subjects with iSCI after leg-cycling predicted lower ankle joint hypertonia and higher Triceps Surae muscle strength, respectively. Conclusion: Leg-cycling modulates cutaneomuscular-conditioned spinal neuronal excitability in healthy subjects and individuals with iSCI, and is related to residual lower limb muscle function. Significance: Cutaneomuscular-conditioned H reflex modulation could be used as a surrogate biomarker of both central neuroplasticity and lower limb muscle function, and could benchmark lower-limb rehabilitation programs in subjects with iSCI.